Cartoon in Form, Function and Meaning Perspectives in Bog-Bog Bali Cartoon Magazine - I Wayan Suandi (Mudra Jurnal Seni Budaya, 2010)
The existence of cartoons in a printing media is a supplement that can even show other side in delivering self mission as social condition indicator of society currenntly. In its development, a cartoon is not an illustration of this media only, but also more dedicated to an opinion and it can even be a promotion media from a product which would like to be presented in this printing media. Thus, the existence of cartoon, a media can improve its role by presenting a more complete menu within simple, humorous drawing language and can attract attention; even a cartoon can speak thousand words.